Hubungan Pola Asuh Otoriter Dan Kecerdasan Emosional Dengan interaksi Teman Sebaya Anak Usia 4-5 Tahun - Putri, Melati Retnandhia (Prosiding University Research Colloquium, 2021)
Peer interaction is a relationship that exists between a group of children with limited membership, which influence each other, which is influenced by various factors. Factors that may influence peer interaction in early childhood are parenting styles and emotional intelligence. The purpose of this study was to determine the effect of authoritarian parenting and emotional intelligence with peer interaction.The variables used in this study are Authoritarian Parenting ( ), Emotional Intelligence ( ) and peer interaction (Y). The population in this study is TK BA in Mungkid District, there are 20 schools with 331 class A students. The sample in this study was 3 BA Kindergarten schools, namely BA Need, BA Bumirejo 1, BA Bumirejo 2 with a group A of 30 students. The sampling technique used is purposive sampling. Methods of data collection using questionnaires and observation techniques. The data analysis technique used multiple linear regression test.The results of the study concluded that there is an influence between authoritarian parenting and emotional intelligence with peer interaction either partially or simultaneously. Partially proven by the acquisition of the t-count value of authoritarian parenting of 4.496 with a sig. 0.000 < 0.05, emotional intelligence also obtained a t-count value of 2.312 with a sig value. 0.029 < 0.05. Simultaneously proved by the acquisition of a calculated F value of 58.716 with a sig value. 0.000 which means that the variables of authoritarian parenting and emotional intelligence together affect peer interaction for early childhood.